An Investigation of the Implicit Endorsement of the Sexual Double Standard Among U.S. Young Adults - Thompson, Ashley E.; Harvey, Carissa A.; Haus, Katherine R.; Karst, Aaron (Frontiers in Psychology, 2020)
Despite empirical support for the sexual double standard (SDS; in which women are judged more harshly than men for engaging in sexual behavior), recent research has demonstrated inconsistencies, perhaps stemming from biased responding in the self-report measures that are commonly used. As a result, researchers are encouraged to adopt innovative methodological procedures to assess the SDS. Thus, the current study investigated the implicit endorsement of the SDS among 147 young adults (71 men, 76 women) using the Implicit Association Test (IAT) and a limited-awareness gender priming procedure. According to our results, young adults endorsed an implicit preference for sexual stimuli (as compared to neutral stimuli) after receiving a male prime in comparison to a female prime, evidence of an implicit SDS. These results indicate that traditional gendered expectations still exist, in which women are judged more harshly than men for engaging in comparable sexual behavior. Implications and recommendations are outlined for clinicians and researchers working to promote gender equality related to one’s sexuality.